Treatment seeking pathway of patients with somatic symptoms attending the outpatient department of a tertiary level psychiatry hospital in Bangladesh (Bangladesh Journal of Psychiatry, 2019)
Patients with somatic symptoms suffered extensively for adopting inappropriate treatment seeking pathway for their treatment. The aim of this study was to determine the treatment seeking pathway of patients with somatic symptoms attending the outpatient department (OPD) of a tertiary care psychiatric hospital in Bangladesh. This was a cross-sectional study conducted from September 2020 to June 2021 among 364 conveniently selected sample of patients with somatic symptoms attending to the OPD of National Institute of Mental Health (NIMH), Bangladesh. Data were collected by face-to-face interview using semi-structured questionnaire after taking the informed consent. After thorough cleaning and editing, the data of 352 respondents were analyzed using statistical package of social sciences (SPSS), version 24. The results showed that, highest percentage (59.9%) of the respondents belonged to the age group of 20-39 years with mean age of 30.64±13.26 years. Majority of them were male (57.7%), Muslim (92.0%) and urban habitant (45.9%). Near about two third (64.3%) respondents sought treatment where 40.7% of them received consultation from non-doctors. Around two-third (65.3%) of the respondents was suggested or referred by a patient or the relative of a patient to get treatment from NIMH. This study came up with valuable information regarding treatments seeking behavior and source of referral of patients to psychiatry center which should be incorporated in policy making to reduce treatment gap and confirm quality health care to the patients with somatic symptoms.Bang J Psychiatry 2019; 33(2): 20-22